Cryopreservation of roe deer abomasal nematodes for morphological identification - Beraldo, Paola; Pascotto, Ernesto (Folia parasitologica, 2014)
Conventional methods to preserve adult nematodes for taxonomic purposes involve the use of fixative or clearing solutions (alcohol, formaldehyde, AFA and lactophenol), which cause morphological alterations and are toxic. The aim of this study is to propose an alternative method based on glycerol-cryopreservation of nematodes for their subsequent identification. Adults of trichostrongylid nematodes from the abomasum of roe deer (Capreolus capreolus Linnaeus) were glycerol-cryopreserved and compared with those fixed in formaldehyde, fresh and frozen without cryoprotectans. Morphology, transparency and elasticity of the anterior and posterior portion of male nematodes were compared, especially the caudal cuticular bursa and genital accessories. The method presented is quick and easy to use, and the quality of nematode specimens is better than that of nematodes fixed by previously used fixatives. Moreover, glycerol cryopreserved nematodes can be stored for a long time at -20 degrees C in perfect condition and they could be suitable for further analyses, such as histological or ultrastructural examinations.
Keywords: Nematoda; hlístice; kryoprezervace; Cryopreservation; nemoci žaludku; zvířata; Cryoprotective Agents; Glycerol; mužské pohlaví; Abomasum; slez; Formaldehyde; formaldehyd; Nematode Infections; Animals; nematodózy; Deer; glycerol; vysoká zvěř; Male; kryoprotektivní látky; Stomach Diseases